2015
DOI: 10.1007/s00221-015-4525-0
|View full text |Cite
|
Sign up to set email alerts
|

Eyeglasses elicit effects similar to face-like perceptual expertise: evidence from the N170 response

Abstract: Studies of event-related potentials show that the specific N170 response has become a stable electrophysiological hallmark of objects related to expertise in early perceptual processing. In the present study, we investigated whether eyeglasses can elicit N170 effects similar to those elicited by objects of expertise. Our results showed that the N170 response elicited by eyeglasses was larger than the response elicited by objects that do not generate perceptual expertise (e.g., houses). Importantly, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These results suggest that mere exposure and visual expertise (Cao et al, 2016) do not entail the type of processing advantages seen for natural faces and face parts.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results suggest that mere exposure and visual expertise (Cao et al, 2016) do not entail the type of processing advantages seen for natural faces and face parts.…”
Section: Discussionmentioning
confidence: 80%
“…Few previous studies tested whether the face processing system learns to respond to evolutionarily novel features and with conflicting results. One fMRI study reported no preferential responses to isolated glasses in the fusiform face area (Axelrod & 4 Yovel, 2011) while an EEG study found that glasses (like faces) can evoke N170 responses, suggesting similarities in perceptual processing (Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Glasses and masks further elicited minimum saccadic reaction times, which were as slow or slower than those for cars, and whole and upper faces. These results suggest that mere exposure and visual expertise ( Cao, Yang, & Hu, 2016 ) do not entail the type of processing advantages seen for natural faces and face parts.…”
Section: Discussionmentioning
confidence: 85%
“…Few previous studies tested whether the face processing system learns to respond to evolutionarily novel features and with conflicting results. One functional magnetic resonance imaging (fMRI) study reported no preferential responses to isolated glasses in the fusiform face area ( Axelrod & Yovel, 2011 ), whereas an electroencephalogram (EEG) study found that glasses (like faces) can evoke N170 responses, suggesting similarities in perceptual processing ( Cao, Yang, & Hu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The original materials were twenty Chinese adults’ upright face pictures with neutral expressions (half of them were male faces) ( Cao et al, 2016 , 2019 ; Zhang et al, 2021 ). Contour features, such as hair and ears, were cropped out using Photoshop (PS), and the isolated face pictures were put against a neutral gray background.…”
Section: Methodsmentioning
confidence: 99%